2002
DOI: 10.1111/1467-8551.00228
|View full text |Cite
|
Sign up to set email alerts
|

Nostalgia and the Narrativization of Identity: A Turkish Case Study

Abstract: This paper offers an interpretation of the collective identity-narrative of a Turkish faculty of vocational education. Particular attention is focused on the importance of nostalgia in acts of collective self-authorship. Nostalgia, it is argued, is key to the understanding of the dynamics of individual and organizational identity-construction in several ways: it can be a means of maintaining a collective sense of socio-historic continuity, a source of resistance to hegemonic influence and a defence against anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
144
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(160 citation statements)
references
References 28 publications
4
144
0
3
Order By: Relevance
“…The studies therefore focus more on individuals' ex-post exploration of the past than the ongoing study of a constructed collective memory. As illustrations, past scholarship has emphasized the importance of considering organizational "biographies" (Kimberly, 1987) or "nostalgia" (Brown & Humphreys, 2002) when analyzing organizations. Yet these and other studies typically rely primarily on a set of individual interviews conducted over a short period of time to study history (for other examples see Biggart (1977), de Holan andPhillips (2004) and Kimberly and Bouchikhi (1995)).…”
Section: Collective Memory and Identity Endurancementioning
confidence: 99%
“…The studies therefore focus more on individuals' ex-post exploration of the past than the ongoing study of a constructed collective memory. As illustrations, past scholarship has emphasized the importance of considering organizational "biographies" (Kimberly, 1987) or "nostalgia" (Brown & Humphreys, 2002) when analyzing organizations. Yet these and other studies typically rely primarily on a set of individual interviews conducted over a short period of time to study history (for other examples see Biggart (1977), de Holan andPhillips (2004) and Kimberly and Bouchikhi (1995)).…”
Section: Collective Memory and Identity Endurancementioning
confidence: 99%
“…For instance, experimental studies have shown that people who were asked to recall nostalgic experiences report a heightened perception of continuity between their past and present selves compared with people who were asked to recall ordinary experiences (Routledge et al, 2006). Qualitative analyses of organizational change also suggest that nostalgia allows individuals to develop a sense of identity continuity (Brown & Humphreys, 2002;Milligan, 2003).…”
Section: Explaining the Positive Consequences Of Nostalgia: Identity mentioning
confidence: 99%
“…Cultural places such as museums are one of the main areas where individuals (re)appropriate objects and images to (re)construct their sense of self and identity (Boym 2001;Goulding 1999aGoulding , 1999bJoy and Sherry 2003). Nostalgia-based experiences in museums provide individuals with a process of 'sense making' (Brown and Humphreys 2002) through which they can relate to broader meanings of life and being. Realization of the potential meanings embedded in the museum exhibits, therefore, depends on individuals' past knowledge of the context to which the texts (the exhibits) belong and also the conditions in which these individuals themselves are presently contextualized.…”
Section: Nostalgia and The Museummentioning
confidence: 99%
“…The museum becomes a workshop of identity and 'self-discovery' (Poulot 1994) where, upon turning the pages of their diary, participants recall their 'inspiring' or/and 'despairing' (Bonnell and Simon 2007) past. Based on visitors' individual and collective narratives of self (Brown and Humphreys 2002), such a workshop can create a variety of conflicting feelings of happiness, sadness, loss, reunion, rejuvenation, aging, pity, fear, pride, shame, guilt, absurdity, hope, esthetic pleasure, and recreation, to name but a few. These diverse feelings can also occur for those who have 'vicarious' experiences of the past (Davis 1979;Goulding 2001).…”
Section: Nostalgia and The Museummentioning
confidence: 99%
See 1 more Smart Citation